Lymphocytic hypophysitis masquerading as transient secondary hyperadrenalism followed by panhypopituitarism - Sharma, Kailash Nath; Malakar, Sayan; Negi, Bhagwan Das; Sharma, Tarun; Kapoor, Dhiraj (Indian Journal of Case Reports, 2019)
Lymphocytic hypophysitis (LH) is a rare inflammatory disease of the pituitary gland. This condition strikingly shows femalepreponderance and commonly affects women during pregnancy or in the post-partum period. It’s a clinical presentation and radiologicalfeatures may mimic pituitary adenoma. Though its treatment modality is uncertain steroid remains the 1st option for treatment. Here,we report an unusual case of LHin a 21-year-old female patient where initially, the patient presented with hyperadrenalism andsecondary hyperthyroidism followed by pan-hypopituitarism (Addisonian crisis) which is attributed to initial autoimmune destructionof the gland followed by subsequent fibrosis. Thus, it is a rare case report which exquisitely explains this rare presentation and suchcases should be investigated thoroughly since there are many differential and response to steroids is remarkable.